College English Assisted Teaching Based on Flipped Classroom and Its Influence on Students' Learning Psychology - Jing Zhang (Hindawi-Wiley, 2022)
English reading occupies a large proportion of English test papers, and English reading ability is crucial for college students. However, in the actual teaching process, teachers often neglect the cultivation of students' reading ability. Influenced by the new crown epidemic, various schools actively carry out online teaching. Through online teaching, we found that students' interest in English classes has significantly increased, and the flipped classroom teaching model is a teaching model that combines online and offline teaching. Therefore, this study attempted to apply the flipped classroom model to college English reading instruction to stimulate students' interest in English reading, increase students' participation in class, and improve students' ability to cooperate with each other and ultimately improve students' reading performance. In this study, independent and paired sample t-tests were conducted using SPSS on the results of two reading tests to analyze the effect of this teaching method on the reading level of college students. The data collected from the questionnaires were quantitatively analyzed to understand the changing status of college students' interest in reading and their perceptions of this instructional model. The study found that the flipped classroom can improve the reading level of college students. As for the survey of students' cultural knowledge in the classroom, 56% of them know more about it, and 44% of them have almost no relevant background knowledge. In summary, we can conclude that students do not do enough prereading before class, their participation in class is low, and they know less about the corresponding cultural background knowledge. In the process of flipped classroom teaching, teachers should focus on adapting to their role change in time and selecting high-quality resources to push to students. At the same time, they should also strengthen the cultivation of students' independent learning ability before class, improve students' initiative, communicate more with students in class, find students' problems in time and give corresponding guidance according to students' specific conditions, and pay attention to the evaluation mode after class. Finally, we give teachers and students corresponding suggestions for the problems that appear in the experimental process, so as to promote the flipped classroom teaching to better serve the college reading teaching.